Crustal structure and geodynamics of the eastern Qilian orogenic belt, NE margin of the Qinghai-Tibet plateau, revealed by teleseismic receiver function - Cheng, Yongzhi; Gao, Rui; Chen, Jiuhui; Lu, Zhanwu; Li, Wenhui; Wang, Guangwen; Chen, Hao; Han, Rubing; Niu, Xiao; Wu, Guowei; Chen, Si; Cai, Yuguo (Frontiers in Earth Science, 2023)
The eastern segment of the Qilian orogenic belt, which is composed of the Linxia block and the Longzhong block, is located at the northeastern margin of the Qinghai–Tibet Plateau. The area has experienced multiple tectonic events, such as the closure of the Qilian Ocean, the convergence of the North China block and the Qilian terrane, and the collision of the Indian and Eurasian plates, forming a complex tectonic framework. To investigate the area's geological evolution and the suture's current location between the blocks, we selected the 3-year data recorded by 33 portable broadband stations of ChinArray II (2013-2016). Using three teleseismic P-wave receiver function methods, H-κ stacking and common conversion point stacking (CCP), the crustal structure, Poisson's ratio, and Moho morphology at 33 stations were obtained. The results of the study showed the following: 1. the Maxianshan fault is an important boundary fault that divides the Linxia block and the Longzhong block. The crustal layered structure of the Linxia block is obvious, and there is a low-velocity anomaly in the middle and lower crust, which may contain saline fluid and has the characteristics of a Japanese-type island arc. 2. The layered structure of the upper crust of the Longzhong block is significant, while the layered structure of the middle and lower crust is weak and presents weak low-velocity characteristics, which has the characteristics of oceanic-island basaltic crust. The Longzhong block may have originally been formed by Mariana-type island arcs. 3. The Conrad interface and the Moho lateral variation in the southwestern margin of the Ordos block are weak, showing the characteristics of a stable craton. 4. Our calculation results show that the Maxianshan fault cuts through the Earth's crust and is a continuous west-dipping negative seismic phase in the CCP section. The fault zone is the suture line between the Linxia block and the Longzhong block. 5. The middle and upper crust of the Liupanshan tectonic belt is thrust upwards on the southwestern margin of the Ordos block. We believe that this is deep structural evidence of the Cenozoic uplift of the Liupanshan structural belt.